2023
DOI: 10.3390/ijms241814201
|View full text |Cite
|
Sign up to set email alerts
|

Development and Characterization of Electrospun Composites Built on Polycaprolactone and Cerium-Containing Phases

Cristiana Plocon,
Alexandru Evanghelidis,
Monica Enculescu
et al.

Abstract: The current study reports on the fabrication of composite scaffolds based on polycaprolactone (PCL) and cerium (Ce)-containing powders, followed by their characterization from compositional, structural, morphological, optical and biological points of view. First, CeO2, Ce-doped calcium phosphates and Ce-substituted bioglass were synthesized by wet-chemistry methods (precipitation/coprecipitation and sol-gel) and subsequently loaded on PCL fibres processed by electrospinning. The powders were proven to be nanom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 64 publications
0
1
0
Order By: Relevance
“…Based on the enzyme-catalyzing ability of CeO 2 , dressings with antimicrobial, anti-inflammatory and antioxidant properties have been developed. For example, when tested by Plocon C et al using human osteoblasts, the composite scaffolds showed very good biocompatibility, with samples consisting of polymers and cerium-doped calcium phosphate responding better ( Plocon et al, 2023 ). Sanmugam A et al found that the fabricated scaffolds completely facilitated the complete closure of the wounds after 14 days, which suggests that the developed scaffolds have high swelling, good degradability and permeability, which facilitated the absorption of wound exudates, thus consolidating the healing effect ( Sanmugam et al, 2024 ).…”
Section: Challenges and Prospectsmentioning
confidence: 99%
“…Based on the enzyme-catalyzing ability of CeO 2 , dressings with antimicrobial, anti-inflammatory and antioxidant properties have been developed. For example, when tested by Plocon C et al using human osteoblasts, the composite scaffolds showed very good biocompatibility, with samples consisting of polymers and cerium-doped calcium phosphate responding better ( Plocon et al, 2023 ). Sanmugam A et al found that the fabricated scaffolds completely facilitated the complete closure of the wounds after 14 days, which suggests that the developed scaffolds have high swelling, good degradability and permeability, which facilitated the absorption of wound exudates, thus consolidating the healing effect ( Sanmugam et al, 2024 ).…”
Section: Challenges and Prospectsmentioning
confidence: 99%